Viral Infection in Adults Hospitalized With Community-Acquired Pneumonia: Prevalence, Pathogens, and Presentation - Johnstone, Jennie (Chest, 2008)
BACKGROUND: The potential role of respiratory viruses in the natural history of community-acquired pneumonia (CAP) in adults has not been well described since the advent of nucleic amplification tests (NATs). METHODS: From 2004 to 2006, adults with CAP who were admitted to five hospitals were prospectively enrolled in the study, and clinical data, cultures, serology, and nasopharyngeal swabs were obtained. NATs from swabs were tested for influenza, human metapneumovirus (hMPV), respiratory syncytial virus (RSV), rhinovirus, parainfluenza virus 1–4, coronaviruses (OC43, 229E, and NL63), and adenovirus. RESULTS: A total of 193 patients were included; the median age was 71 years, 51% of patients were male, and 47% of patients had severe CAP. Overall, 75 patients (39%) had a pathogen identified. Of these pathogens, 29 were viruses (15%), 38 were bacteria (20%), 8 were mixed (4%), and the rest were “unknown.” Influenza (n = 7), hMPV (n = 7), and RSV (n = 5) accounted for most viral infections; other infections included rhinovirus (n = 4), parainfluenza (n = 3), coronavirus (n = 4), and adenovirus (n = 2). Streptococcus pneumoniae was the most common bacterial infection (37%). Compared with bacterial infection, patients with viral infection were older (76 vs 64 years, respectively; p = 0.01), were more likely to have cardiac disease (66% vs 32%, respectively; p = 0.006), and were more frail (eg, 48% with limited ambulation vs 21% of bacterial infections; p = 0.02). There were few clinically meaningful differences in presentation and no differences in outcomes according to the presence or absence of viral infection. CONCLUSIONS: Viral infections are common in adults with pneumonia. Easily transmissible viruses such as influenza, hMPV, and RSV were the most common, raising concerns about infection control. Routine testing for respiratory viruses may be warranted for adults who have been hospitalized with pneumonia.